2000
DOI: 10.1159/000018489
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Spectrum of HPV Types Detected in Cutaneous Squamous-Cell Carcinomas Depend on the HPV Detection System: A Comparison of Four PCR Assays

Abstract: Background: The association of human papillomavirus (HPV) with cutaneous squamous-cell carcinomas (SCCs) has been described recently, but the frequency and spectrum of HPV types identified differed substantially in distinct studies. Objective: Comparison of different PCR assays with respect to sensitivity and range of HPV types detected. Method: Cutaneous SCC were analyzed for HPV DNA using both consensus PCR assays with degenerate primers and PCR assays with nondegenerate primers derived from HPV types 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 24 publications
1
42
1
2
Order By: Relevance
“…This difference could be explained by the fact that in our study a specific HPV38 set of primers was used rather than consensus and/or degenerate primers. Indeed, it has been shown that different PCR assays impact on the frequency and spectrum of cutaneous HPV types detected in skin lesions (33).…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be explained by the fact that in our study a specific HPV38 set of primers was used rather than consensus and/or degenerate primers. Indeed, it has been shown that different PCR assays impact on the frequency and spectrum of cutaneous HPV types detected in skin lesions (33).…”
Section: Discussionmentioning
confidence: 99%
“…28 The finding that viral load in cutaneous tumors was 1 HPV DNA/ 20-5000 tumor cells, pointed out that not every tumor cell harbours HPV genome. 11,25,29 This finding explains that why we need highly sensitive detection techniques to show HPV DNA in the lesions. It was reported that HPV could not be detected with degenerate PCR and other techniques in up to 40% of cutaneous warts which were known to develop as a consequence of active infection with HPV.…”
Section: Discussionmentioning
confidence: 99%
“…30 Due to the low viral load in tumor cells, the frequency and spectrum of HPV detected by different techniques with different sensitivities show a great diversity. 25 In PCR technique, while degenerate primers enable detection of a broad range of HPV types with limited sensitivity for different HPV types, nondegenerate primers allow detection of only small subset of HPV types but with high sensitivity. 25 To detect all HPVpositive cases, several degenerate PCR primers should be combined with multiple nondegenerate PCR primers, each of which is specific for different HPV types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[7][8][9][10] Acredita-se que cerca de 15% das neoplasias sejam de origem viral. Além do HPV, outros vírus são descritos como oncogenes, como o vírus da hepatite C e alguns herpes-vírus humanos (HHV).…”
Section: Introductionunclassified